The asymmetrical structure of Golgi apparatus membranes revealed by in situ atomic force microscope. - Haijiao Xu; Weiheng Su; Mingjun Cai; Junguang Jiang; Xianlu Zeng; Hongda Wang (PLoS ONE, 2013)
The Golgi apparatus has attracted intense attentions due to its fascinating morphology and vital role as the pivot of cellular secretory pathway since its discovery. However, its complex structure at the molecular level remains elusive due to limited approaches. In this study, the structure of Golgi apparatus, including the Golgi stack, cisternal structure, relevant tubules and vesicles, were directly visualized by high-resolution atomic force microscope. We imaged both sides of Golgi apparatus membranes and revealed that the outer leaflet of Golgi membranes is relatively smooth while the inner membrane leaflet is rough and covered by dense proteins. With the treatment of methyl-β-cyclodextrin and Triton X-100, we confirmed the existence of lipid rafts in Golgi apparatus membrane, which are mostly in the size of 20 nm -200 nm and appear irregular in shape. Our results may be of significance to reveal the structure-function relationship of the Golgi complex and pave the way for visualizing the endomembrane system in mammalian cells at the molecular level.